1998
DOI: 10.1246/cl.1998.905
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Alkenylruthenium(II) Complexes with Hydrosilane: C-Si vs C-H Bond Formation

Abstract: Alkenylruthenium complexes, Ru{C(R1)=CH(R2)}Cl(CO)(PPh3)2 (R1 = H, R2 = Ph; R1 = H, R2 = t-Bu; R1 = Ph, R2 = Ph; R1 = CH=CH(SiMe3), R2 = SiMe2Ph), react with HSiMe2Ph via two reaction courses (path A and path B), leading to C–Si and C–H bond formation, respectively. Relative ratio of the two courses is strongly dependent upon steric bulkiness of substituent(s) on the alkenyl ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In this paper we wish to report our mechanistic studies on the reactions of alkenylruthenium(II) complexes with hydrosilanes . Since 1a in Scheme is too unstable to be isolated, further study on the mechanisms of C−Si and C−H bond formation was infeasible.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we wish to report our mechanistic studies on the reactions of alkenylruthenium(II) complexes with hydrosilanes . Since 1a in Scheme is too unstable to be isolated, further study on the mechanisms of C−Si and C−H bond formation was infeasible.…”
Section: Introductionmentioning
confidence: 99%
“…While the C−Si bond formation from alkyl(silyl)platinum complexes is the most widely accepted product-forming step for platinum-catalyzed hydrosilylation of alkenes, , little is known about this elementary process. We recently reported that cis -PtMe(SiPh 3 )L 2 complexes (L = PMePh 2 , PMe 2 Ph) readily afford MeSiPh 3 in quantitative yields in solution. , This reaction is effectively accelerated by alkynes and alkenes added to the systems, particularly by those with electron-withdrawing substituents. Kinetic studies indicated that the MeSiPh 3 formation in the presence of diphenylacetylene proceeds via the mechanism involving prior replacement of one of the phosphine ligands (L) with diphenylacetylene, followed by reductive elimination of MeSiPh 3 from the resulting [PtMe(SiPh 3 )(PhC⋮CPh)(L)] intermediate.…”
Section: Introductionmentioning
confidence: 99%